Sosialisasi Tentang Deteksi Diagnosis Dan Pencegahan Penyakit Tidak Menular - Aini; Rizal Pratama Adiputra; Yan Reiza Permana (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Morbidity or death caused by non-communicable diseases (NCD) is about 63% of all deaths. The goal to be achieved after this service is that the end result of this socialization is that at least 70% of participants can understand how to detect, diagnose and treat non-communicable diseases (NCDs). (3) The implementation of this activity is through socialization to the community in Gelogor Village in collaboration with the P3MD MFH Polytechnic, Gelogor Village Head, Family Hope Program (PKH). Services are carried out through socialization. Monitoring and evaluation is carried out in the form of a questionnaire given before and after socialization. The conclusion of this service activity has been that there has been socialization and an increase in the value of correct answers on socialization from 40% to 80%.